Anbbreviated clinical study reports with investigational medicinal products for human use : current gudelines and recommendations - Alfaro, Vicente (Array, 2007)
Extensive and complete documentation must be submitted for obtaining a marketing authorization of an investigational medicinal product in the European Union, Japan, or the United States.One of the most critical of the documents submitted as part of the Common Technical Document, masterpiece of a marketing authorization application, is the Clinical Study Report, which represents the integrated full report of efficacy and safety data for an individual study of a therapeutic or diagnostic agent.The content and format of a Clinical Study Report is recommended by the International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) guideline E3 on Structure and Content of Clinical Study Reports, which was approved in 1996.Some of the studies conducted during product development may ultimately not contribute to the evaluation of the effectiveness of a product for a specific indication.In these cases, abbreviated Clinical Study Reports are required to be submitted to the regulatory authorities.However, the ICH E3 guideline only provides information on the structure and content of full Clinical Study Reports.A guideline issued by the Food and Drug Administration of the United States in 1999 is the only document available from a regulatory authority that recommends which sections can be included in an abbreviated Clinical Study Report.This article describes which sections have to be included in abbreviated Clinical Study Reports written during clinical development of new medicinal products for human use